Person(s) of Interest and Missing Women: Legal Abandonment in the Downtown Eastside - Craig, Elaine (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2014)
The criminal prosecution of Robert Pickton involved an eleven-month jury trial, two appeals to the British Columbia Court of Appeal, an appeal to the Supreme Court of Canada, and seventy-six reported judicial rulings. This article, through a combination of discursive and doctrinal analyses of these seventy-six decisions, examines what was (not) achieved by the Pickton trial. It discusses three areas: the judicial representation of the women Pickton was prosecuted for murdering; the implications of the jury’s verdict in the Pickton proceedings; and the impact of the Pickton trial on the families of the women he murdered. The article starts from the premise that it is correct to characterize these murders as a product of collective violence. Colonialism, political and legal infrastructure, and public discourse—and hegemonies based on race, class, and gender that these processes, institutions, and practices hold in place—produced a particular class of vulnerable women, the police who failed them, and Robert Pickton. The article concludes by suggesting that the outcomes of the Pickton prosecution both highlight the limitations of the criminal justice system and offer an analytical framework for examining other institutional responses (such as the Missing Women’s Inquiry) to the kind of collective violence that gave rise to the Pickton circumstance.